The role of risk climate and ethical self-interest climate in predicting unethical pro-organisational behaviour - Sheedy, Elizabeth A. (Journal of business ethics, 2021)
Unethical pro-organisational behaviour (UPB) is an ongoing concern, prompting the need for more nuanced understanding of the workplace environment most likely to inhibit it. This study considers the role of risk climate, sometimes referred to as risk culture, as well as ethical climate, for reducing UPB. The study investigates whether four risk climate factors (avoidance, valued, proactive and manager) can, by focusing on the long-term consequences of UPB to the organisation, and providing guidance on behavioural norms, reduce UPB misconduct. Surveying employees in three financial institutions we found that only one of the risk climate factors, avoidance, is consistently associated with UPB. On the other hand, a self-interested, (un)ethical climate significantly increases UPB in all samples. In multi-climate analysis, we found that risk climate factors interacted with ethical climate to predict UPB. That is, when employees perceive that the workplace ethos is not self-interested, three factors of risk climate—avoidance, proactive and manager—significantly predict UPB. UPB is least likely when self-interest is low, avoidance risk climate is low, proactive risk climate is high and manager risk climate is high. Implications for leaders are discussed.